2007
DOI: 10.1203/pdr.0b013e31802d89eb
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Urinary Cotinine Correlates With Behavioral Alterations in Newborns Prenatally Exposed to Tobacco Smoke

Abstract: Altered behavior due to prenatal smoke exposure was examined in 25 neonates born from smoking mothers who consumed at least 5 cigarettes/d during the entire gestation. Data were compared with 25 matched neonates born from nonsmoking mothers. Neonatal behavior was evaluated using the Brazelton Neonatal Behavioral Assessment Scale (BNBAS). Antenatal exposure to tobacco smoke at the end of the pregnancy was determined by measurement of urinary cotinine. Newborns from smoking mothers showed significant lower score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 25 publications
3
37
2
3
Order By: Relevance
“…There is also a greater likelihood of exposed infants to be admitted into the neonatal intensive care unit relative to unexposed controls (Adams et al, 2002). Newborns exposed in utero to nicotine are more irritable and have poorer attention than unexposed infants, and they exhibit hypertonicity, increased tremors and startle responses, and deficient speech processing as well (Espy et al, 2011;Key et al, 2007;Mansi et al, 2007;Reijneveld et al, 2002;Stroud et al, 2009a). Within the first month of life, exposed infants show signs of poorer self-regulation and require more handling by caregivers (Stroud et al, 2009b).…”
Section: Tobacco/nicotinementioning
confidence: 99%
See 1 more Smart Citation
“…There is also a greater likelihood of exposed infants to be admitted into the neonatal intensive care unit relative to unexposed controls (Adams et al, 2002). Newborns exposed in utero to nicotine are more irritable and have poorer attention than unexposed infants, and they exhibit hypertonicity, increased tremors and startle responses, and deficient speech processing as well (Espy et al, 2011;Key et al, 2007;Mansi et al, 2007;Reijneveld et al, 2002;Stroud et al, 2009a). Within the first month of life, exposed infants show signs of poorer self-regulation and require more handling by caregivers (Stroud et al, 2009b).…”
Section: Tobacco/nicotinementioning
confidence: 99%
“…Within the first month of life, exposed infants show signs of poorer self-regulation and require more handling by caregivers (Stroud et al, 2009b). Newborns also demonstrate an attenuated response to auditory stimuli, an effect that can contribute to language and learning impairments later in life (Kable et al, 2009;Mansi et al, 2007).…”
Section: Tobacco/nicotinementioning
confidence: 99%
“…Numerous studies spanning several decades have found differences in arousal, attention, reaction to stress, and soothability between tobacco-exposed (TE) and non-exposed (NE) neonates (Espy et al, 2011; Jacobson, Fein, Jacobson, Schwartz, & Dowler, 1984; Mansi et al, 2007; Stroud et al, 2009). In contrast, there is a relative dearth of research examining the effects of PTE on infant self-regulation beyond the first month of life.…”
Section: Pte and Infant Self-regulationmentioning
confidence: 99%
“…[29] ont démontré de façon tout à fait claire, dans une étude incluant 50 nouveaunés, que la cotinurie mesurée à la naissance était prédictive des modifications de comportement à type d'irritabilité, de troubles de l'attention ou de difficultés de réponses à un stimulus, observées plus tard chez ces nourrissons.…”
Section: Urineunclassified